Family Planning and Climate Change - Reyer Gerlagh; Veronica Lupi; Marzio Galeotti (Center for Economic Studies and ifo Institute (CESifo), 2018)
The historical increase in emissions is for one-fourth attributable to the growth of emissions per person, whereas three-fourths are due to population growth. This striking evidence is not represented in the majority of climate-economic studies, which mostly neglect the environmental consequences of individuals' reproductive decisions. In this paper, we study the interactions between climate change and population dynamics. We develop an analytical model of endogenous fertility and embed it in a calibrated climate-economy model. Our results present family planning as an integral part of climate policies and quantify the costs of neglecting the interaction.
Keywords: J11; J13; H23; Q54; Q56; 330; fertility; climate change; population; carbon tax; fertility tax; climate-economy models